Development of an On-line Vibration Based Fault Detection Systems for an Electric Mining Shovel - Markus Timusk (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
This paper describes a research project that focuses on developing a diagnostic routine to assist in decision support for the condition based maintenance of mobile mining equipment subject to unsteady duty. The objective is to develop a general method for initial identification of mechanical faults in machinery operating under non-steady state conditions. The platform to be used for the experimental development and validation of the system is the swing machinery in an electric mining shovel operating in an open pit mining environment. The strategic approach that is proposed for the diagnostic routine will involve using novelty detection augmented by temporal classification.